PO151 Infections in patients with multiple sclerosis on alemtuzumab – should antibiotic prophylaxis be standard?. (1st December 2017) - Shafei, Rachelle; Fourali, Samih; Hateley, Sofie; Dubuisson, Nicolas; Davidson, Harriet; Turner, Benjamin; Gnanapavan, Sharmilee; Giovannoni, Gavin; Schmierer, Klaus
Abstract : Background: Alemtuzumab is an effective disease modifying treatment (DMT) for people with relapsing multiple sclerosis (pwRMS). Its mechanism of action includes profound lymphocyte depletion. Objective: To analyse the pattern of lymphocyte depletion and associated infections after alemtuzumab administration in a cohort of pwRMS treated at our centre. Methods: pwRMS treated with alemtuzumab were identified on our clinical record system (Cerner Millennium). Baseline blood results, total lymphocyte counts (TLC) and infections post-treatment were studied. Results: 84 pwMS on alemtuzumab were followed up for a mean of 8.7 months. One month after the first treatment cycle, TLC was 13% of baseline (from 2.2 to 0.28 × 109/l). TLC recovered to >0.6 by month 3 and to >1 by month 9, however remained below baseline in all pwRMS. After the 2nd treatment cycle, TLC reconstitution was more rapid, to >1×109/l within six months. 19 (23%) pwRMS had infections within four months of treatment cycles. Infections affected the respiratory tract in 7 (8%) pwRMS, and the urinary tract in 9 (11%). All but one infection occurred with TLC <0.6. Conclusion: Infections are common in pwRMS treated with alemtuzumab. To reduce their incidence prophylactic antibiotics should be considered in pwRMS with TLC of <0.6×109/l.